Push-Out Bond Strength of Calcium Silicate-Based Cements in the Presence or Absence of a Smear Layer - Ahmad S. Al-Hiyasat; Wafa'a A. Yousef (Hindawi Limited, 2022)
Objectives. Variations between the material compositions and the presence of a smear layer on the dentin surface may influence the bond strength of the material, thus this study evaluated the push-out bond strength of different calcium silicate materials to root dentin in the presence or absence of smear layer. Materials and Methods. The palatal canal of sixty maxillary first premolars were prepared and divided into three groups according to the materials to be used: ProRoot WMTA, Biodentine, and TotalFill FS. Each group was then divided into two subgroups; with and without a smear layer. Roots were sectioned into three slices and filled with the tested materials. Push-out bond strength of materials was measured by universal machine. Results. Bond strength of Biodentine was significantly higher than the MTA and TotalFill FS in the presence or absence of smear layer. Overall, removing the smear layer reduced the bond strength of the three materials. The reduction was significant for MTA and TotalFill FS but not for Biodentine. Conclusions. Biodentine demonstrated the highest bond strength to radicular dentin followed by MTA, and then TotalFill FS. Overall, removal of the smear layer from dentin surface reduced the bond strength of the calcium silicate root repair materials.